Schooling in a prision environment - Guimarães, Ana Paula (2022)
Schooling and learning are fundamental in the development of a society, whatever it may be, they are the engine of progress and evolution. We conducted this study in order to understand the level of schooling of the Portuguese prison population. For this purpose, we used the data from the most recent official sources available and the most pertinent national legislation. We concluded that the Portuguese prison population is characterised by having a low level of schooling and we searched for the solutions legally foreseen to overcome this deficit in the population concerned. In fact, the law provides for education, vocational training, work and occupational activities as a way to contribute to the social reintegration of the inmate. It should not be forgotten that today's prisoners will be free tomorrow and that social reintegration is also done this way: by teaching and educating, providing tools to prisoners so that in the future they can adopt a socially responsible life. Schooling and learning are unquestionable capitals for social integration, for obtaining employment, for participation in civic life, for the rebirth of life of an ex-prisoner and education is a fundamental right of all citizens, foreseen in the Constitution of the Portuguese Republic.